Use of Direct Method in Arabic Vocabulary Learning for Arabic Language Teachers at Muhammadiyah Schools in DKI Jakarta : Bahasa Indonesia - Zainul Abidin; Amin Fauzi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Language has four components including sound, vocabulary, structure and meaning. In learning foreign languages, especially Arabic, these four components must be taught to students. In order for learning to get better results, it must be taught using the right method. Each language component already has a learning method. As for learning Arabic vocabulary, one of the methods is the direct method. The purpose of this community service activity is so that Arabic language teachers in Muhammadiyah schools in DKI Jakarta can increase their pedagogical competence in learning Arabic vocabulary so that the resulting learning can be better. The target of the service is Arabic language teachers in Muhammadiyah schools throughout DKI Jakarta. The activity will be carried out online on Thursday, December 23, 2021, at 08.30 to 11.45 WIB. The stages of the activity include answering pretest questions, training insights related to the direct method, teacher panel discussions from the material presented, answering posttest questions. The results of the teacher's activities can understand Arabic vocabulary learning by using the direct method. The continuation of the program implementation is by monitoring the teachers to apply it in learning Arabic vocabulary in the classroom. Implementing the activities of lecturers and students and assisted by the DKI Jakarta PWM Educational Council.